El valor probatorio de la prueba por indicios en el nuevo proceso penal - García Cavero, Percy (Revista de Derecho, 2019)
The present article deals with the evidentiary value of the so-called circumstantial evidence. It starts by making some general considerations such as concept, denomination and elements, to then describe the diverse phases involved in the process of producing such evidence in the new structure of the penal process. In the last part of the work the requisites needed for this evidentiary modality to acquire evidential value in terms of proving allegations from the parts in the penal process are mentioned and developed alongside with the national legislation and jurisprudence.
Keywords: Circumstantial evidence; indirect evidence; indication; evidentiary value